The immediate adverse drug reactions induced by ShenMai Injection are mediated by thymus-derived T cells and associated with RhoA/ROCK signaling pathway - Jiang, Shan; Sun, Bo; Zhang, Yan; Han, Jiayin; Zhou, Yanyan; Pan, Chen; Wang, Hongjie; Si, Nan; Bian, Baolin; Wang, Linna; Wang, Lifang; Wei, Xiaolu; et al. (Frontiers in Immunology, 2023)
The mechanism of the immediate adverse drug reactions (ADRs) induced by ShenMai injection (SMI) has not been completely elucidated. Within 30 minutes, the ears and lungs of mice injected with SMI for the first time showed edema and exudation reactions. These reactions were different from the IV hypersensitivity. The theory of pharmacological interaction with immune receptor (p-i) offered a new insight into the mechanisms of immediate ADRs induced by SMI. In this study, we determined that the ADRs were mediated by thymus-derived T cells through the different reactions of BALB/c mice (thymus-derived T cell normal) and BALB/c nude mice (thymus-derived T cell deficient) after injecting SMI. The flow cytometric analysis, cytokine bead array (CBA) assay and untargeted metabolomics were used to explain the mechanisms of the immediate ADRs. Moreover, the activation of the RhoA/ROCK signaling pathway was detected by western blot analysis. In BALB/c mice, the vascular leakage and histopathology results showed the occurrence of the immediate ADRs induced by SMI. The flow cytometric analysis revealed that CD4+ T cell subsets (Th1/Th2, Th17/Treg) were imbalanced. And the levels of cytokines such as IL-2, IL-4, IL12P70 and INF-γ increased significantly. However, in BALB/c nude mice, all the indicators mentioned above have not changed significantly. The metabolic profile of both BALB/c mice and BALB/c nude mice was significantly changed after injecting SMI, and the notable increase in lysolecithin level might have a greater association with the immediate ADRs induced by SMI. The Spearman correlation analysis revealed that LysoPC (18:3(6Z,9Z,12Z)/0:0) showed a significant positive correlation with cytokines. After injecting SMI, the levels of RhoA/ROCK signaling pathway-related protein increased significantly in BALB/c mice. Protein-protein interaction (PPI) showed that the increased lysolecithin levels might be related to the activation of the RhoA/ROCK signaling pathway. Together, the results of our study revealed that the immediate ADRs induced by SMI were mediated by thymus-derived T cells, and elucidated the mechanisms of such ADRs. This study provided new insights into the underlying mechanism of immediate ADRs induced by SMI.